Carboxypeptidase A immobilization with zeolitic imidazolate framework for enhancement of ochratoxin A degradation ability. Issue 1 (1st January 2020) - Ma, Lei; Qiu, Xi; Li, Yaqi; Tang, Sheng; Shen, Wei; Xing, Changrui; Kong, Dezhao; Sheng, Jianguo
ABSTRACT: Ochratoxin A (OTA) is a highly toxic potential contaminant of most agricultural products, and OTA is difficult to remove in general food production processes. In this study, we immobilized polyvinyl pyrrolidone-coated carboxypeptidase A (CPA) into zeolitic imidazolate framework material to improve the ability for OTA degradation. In this method, carboxypeptidase A was dispersed well in the material and maintained its stability and ability to degrade OTA, under complex matrix conditions with better repeated use performance than free carboxypeptidase A. The substrate conversion rate of CPA increased 3 times after immobilization. After repeated use of 10 cycles, the composite enzyme still retained 71.37% of its initial activity. The degradation rate of OTA was 30.69% higher than that of free CPA. This method may play an important role in the degradation of mycotoxins.